La santé publique en vallée d’Ossau (Béarn, France) aux XVIIIe et XIXe siècles à partir de la démographie et des écrits - Frédéric Bauduer; Jean-Pierre Dugène (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
In order to explore the health status of Pyrenean populations during the 18th and 19th centuries, demographic data from the death/burial registers of Arudy, Bilhères and Béost, three villages in the Ossau valley (historic province of Bearn, France), were interpreted in the light of various written sources (scientific publications and official documents). In comparison with a panel of contemporary populations, the indicators analysed seem favourable as regards overall and infant mortality and the seasonality of deaths. Evidence appeared of mortality crises evoking epidemics and mainly involving children, especially during the 18th century. This article reviews the health determinants that could account for this profile, mainly considering extrinsic factors related to the environment, social organization, living conditions and the healthcare armamentarium.